Telaah Korupsi Pt Timah Tbk Menurut Implementasi Hukum Perusahaan Indonesia - Gustiawan Putra, Ido; Setyawan, Fendy; Fahamsyah, Ermanto (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2024)
This paper analyzes the corruption of PT Timah Tbk using Indonesian corporate law perspective based on Law Number 19 of 2003 concerning BUMN and Law Number 40 of 2007 concerning Limited Liability Companies. This research method is normative with a normative juridical approach, namely the study of PT Timah Tbk's corruption using laws and regulations in the form of Law Number 19 of 2003 concerning BUMN and Law Number 40 of 2007 concerning Limited Liability Companies and various other literature. This paper aims to examine whether or not the rules of Indonesian corporate law in accordance with Law Number 19 of 2003 concerning BUMN and Law Number 40 of 2007 concerning Limited Liability Companies are implemented in the governance of PT Timah Tbk. The results of this study show that Law No. 19 of 2003 and Law No. 40 of 2007 are not optimally implemented, resulting in corruption that causes state losses.